A circumplex approach to (de)motivating styles in physical education: Situations-In-School–Physical Education Questionnaire in Spanish students, pre-service, and in-service teachers - Burgueño Menjibar, Rafael; Abós, Ángel; Sevil-Serrano, Javier; Haerens, Leen; De Cocker, Katrien; García-González, Luis (Taylor & Francis, 2024)
Building upon self-determination theory and the circumplex approach, the objective of this study was to adapt the Situations-in-School–Physical Education (SIS–PE) questionnaire and to gather validity and reliability evidence in the Spanish PE context. Three samples of 1441 students (46.43% girls), 473 in-service teachers (35.73% women), and 654 pre-service teachers (50.31% women) participated. Multidimensional scaling analyses indicated that (de)motivating styles (autonomy support, structure, control, and chaos) were graphically depicted by a two-dimensional circular structure differing into need-supportiveness (horizontal axis) and teacher directiveness (vertical axis). Eight specific approaches (two per stye) were additionally identified (participative, attuning, guiding, clarifying, demanding, domineering, abandoning, and awaiting) drawing an ordered pattern of correlations. Bifactor exploratory structural equation modeling additionally supported four overarching styles and eight specific approaches. Reliability and external validity were met in the three samples. The Spanish versions of the SIS-PE questionnaire are valid and reliable measures to assess students’, in-service, and pre-service teachers’ perceptions of (de)motivating styles.
https://openpolicyfinder.jisc.ac.uk/id/publication/5844?from=single_hit
Keywords: Educación física - Estudio y enseñanza; Profesores de educación física; Pedagogía; Need-supportive style; Need-thwarting style; Teaching style; Teaching behavior; Circumplex model